Grado en geografía y ordenación del territorio. Contrastividad del Prácticum y TFG - Cejudo Mejías, Vanesa; Oliva Marañón, Carlos (TECHNO Review. International Technology, Science and Society Review / Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
La Geografía, acuñada como vocablo por Eratóstenes de Cirene, se configura como una ciencia desde el siglo XIX. Los objetivos de esta investigación son realizar un análisis contrastivo de la carga lectiva en créditos ECTS de las asignaturas Prácticum y Trabajo de Fin de Grado distribuidos tanto en el Grado en Geografía como en el Grado en Geografía y Ordenación del Territorio en las Universidades españolas Se ha realizado una comparativa por créditos ECTS, cursos y cuatrimestres. Los resultados verifican la homogeneidad atinente al Prácticum distribuido en 6 créditos ECTS y la heterogeneidad relativa al Trabajo de Fin de Grado.
Bachelor´s degree in geography and land planning: contrastivity of the practicum and bachelor thesis
Geography, coined as a word by Eratosthenes of Cyrene, has been configured as a science since the 19th century The objectives of this research are to carry out a contrastive analysis of the teaching load in credits ECTS of the practicum and bachelor thesis distributed both in the Degree in Geography and in the Degree in Geography and Territory Planning in Spanish Universities. A comparison has been made by ¨ECTS¨ credits, courses and semesters. The results verify the homogeneity regarding the Practicum distributed in 6 ECTS credits and the relative heterogeneity of the bachelor thesis.
Keywords: Grado en Geografía; Grado en Geografía y Ordenación del Territorio; Trabajo de Fin de Grado (TFG); Prácticum; Universidades españolas; comparativa universitaria; Bachelor thesis; Degree in Geography; Degree in Geography and Land Planning; Practicum; Spanish Universities; university comparison; Scopus